The Effect of Water Filtration on Cholera Mortality - Daniel Knutsson (Research Institute of Industrial Economics (IFN), 2020)
There is debate among researchers regarding the importance of water filtration in reducing mortality during the epidemiological transition. However, there is limited research on how water filtration affected cholera mortality during the second half of the 19th century. Using historical microdata, this paper provides new evidence on the importance of water filtration in reducing cholera mortality during an outbreak. The results show that access to filtered water protected almost completely against cholera mortality. Water filtration could thereby have contributed more to mortality decline than what has previously been documented.
Keywords: I11; I18; N3; H51; 330; Water; Piped water; Filtered water; Cholera; Mortality; Public health